Costs and healthcare use of patients with chronic kidney disease in the Northern Territory, Australia - Winnie Chen; Kirsten Howard; Gillian Gorham; Asanga Abeyaratne; Yuejen Zhao; Oyelola Adegboye; Nadarajah Kangaharan; Mohammad Radwanur Rahman Talukder; Sean Taylor; Alan Cass; Territory Kidney Care Steering Committee (BMC, 2024)
Abstract Background The burden of chronic kidney disease (CKD) is high in the Northern Territory (NT), Australia. This study aims to describe the healthcare use and associated costs of people at risk of CKD (e.g. acute kidney injury, diabetes, hypertension, and cardiovascular disease) or living with CKD in the NT, from a healthcare funder perspective. Methods We included a retrospective cohort of patients at risk of, or living with CKD, on 1 January 2017. Patients on kidney replacement therapy were excluded from the study. Data from the Territory Kidney Care database, encompassing patients from public hospitals and primary health care services across the NT was used to conduct costing. Annual healthcare costs, including hospital, primary health care, medication, and investigation costs were described over a one-year follow-up period. Factors associated with high total annual healthcare costs were identified with a cost prediction model. Results Among 37,398 patients included in this study, 23,419 had a risk factor for CKD while 13,979 had CKD (stages 1 to 5, not on kidney replacement therapy). The overall mean (± SD) age was 45 years (± 17), and a large proportion of the study cohort were First Nations people (68%). Common comorbidities in the overall cohort included diabetes (36%), hypertension (32%), and coronary artery disease (11%). Annual healthcare cost was lowest in those at risk of CKD (AUD$7,958 per person) and highest in those with CKD stage 5 (AUD$67,117 per person). Inpatient care contributed to the majority (76%) of all healthcare costs. Predictors of increased total annual healthcare cost included more advanced stages of CKD, and the presence of comorbidities. In CKD stage 5, the additional cost per person per year was + $53,634 (95%CI 32,769 to 89,482, p < 0.001) compared to people in the at risk group without CKD. Conclusion The total healthcare costs in advanced stages of CKD is high, even when patients are not on dialysis. There remains a need for effective primary prevention and early intervention strategies targeting CKD and related chronic conditions.